Jasmonate Signaling Methods and Protocols - Goossens, Alain.; Goossens, Alain.; Pauwels, Laurens.; Pauwels, Laurens. (Methods in Molecular Biology, 2013)
It is now well established that jasmonates, originally identified as the major component of jasmine scent, play a universal role in the plant kingdom and are involved in the regulation of diverse aspects of plant biology, including growth, development, metabolism, and interaction with the environment.  In Jasmonate Signaling: Methods and Protocols, experts in the field aim to unite powerful emerging omics platforms with a number of key reductionist approaches to form a comprehensive collection of tools and protocols. The detailed chapters in this book embrace physiological, environmental, molecular, omics, and bioinformatics approaches that allow dissecting jasmonate actions in the model species Arabidopsis thaliana or in other plants.  Written in the highly successful Methods in Molecular Biology series format, chapters feature introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, along with tips on troubleshooting and avoiding known pitfalls.   Authoritative and cutting-edge, Jasmonate Signaling: Methods and Protocols will empower interested researchers to dissect all steps of jasmonate signaling and the processes they modulate.